PERILAKU MENCARI PENGOBATAN (Health Seeking Behavior) PADA PENDERITA HIPERTENSI - Fitra Galih Nonasri (Jurnal Medika Hutama, 2021)
Background : Hypertension is still a cause of sudden death because it is asymptomatic and without complaints. The condition of blood vessel pressure in patients with hypertension has a persistent increase characterized by systolic pressure exceeding 140 mmHg and diastolic> 90 mmHg when repeated examinations are performed in a resting state. Hypertension is a non-communicable disease which is one of the main causes of premature death in the world with a prevalence of 22% of the world's population. The high number of hypertension sufferers is known to be less than one fifth of those who make efforts to control blood pressure, even though hypertension sufferers should take long-term treatment to control blood pressure and so that complications do not arise. Methods : This literature review is from 2 books, data from the ministry of health, data from the Central Bureau of Statistics, 3 national journals, and 13 international journals. The source search process is carried out through the database of the Ministry of Health, the Central Bureau of Statistics, PubMed, and Google Scholar. Result : The results of the literature study consist of the characteristics of hypertension sufferers which are described based on age, gender, education level, and place of residence. In addition, it also describes the pattern of treatment-seeking behavior carried out by people with hypertension.